Предмет: Алгебра, автор: dimaonopko2020

Обчисліть \frac{5^{-3,8} 25^{6,4} }{125^{\frac{2}{3} } (625^{-0,1})^{-10} } } -64^{\frac{1}{6} }

Ответы

Автор ответа: onlainhelp
3

\frac{5^{-3,8}* 25^{6,4}  }{125^{\frac{2}{3} }(625^{-0,1})^{-10}  }-64^{\frac{1}{6} }  =\frac{5^{-3,8} * (5^{2})^{6,4}  }{(5^{3})^{\frac{2}{3} }*(5^{4} )^{-0,1*(-10)}   } -(2^{6} )^{\frac{1}{6} } =\frac{5^{-3,8}*5^{2*6,4}  }{5^{3*\frac{2}{3} } *5^{4} } -(2^{6*\frac{1}{6} } )=\frac{5^{-3,8}*5^{12,8}  }{5^{2}*5^{4}  } -2^{1} =\frac{5^{-3,8+12,8} }{5^{2+4} } -2=\frac{5^{9} }{5^{6} } -2=5^{9-6} -2=5^{3} -2=125-2=123

Объяснение:

5^{2} =25

5^{3} =125

5^{4} =625

2^{6} =64

Похожие вопросы